DINAMIKA KEMISKINAN DI INDONESIA : ANALISIS PEMBIAYAAN SYARIAH, PENDIDIKAN, DAN KETIMPANGAN (2015-2025) - Enjang Ryan Firmansyah; Mohammad Hamdan Nurhadi; Umamah Mumtazah Askhiyah; Syaeful Bakhri; Abdul Aziz (ITB AAS INDONESIA Surakarta, 2026)
This study aims to examine the effect of Islamic financing, education, and inequality on poverty in Indonesia. This research employs a quantitative approach using secondary panel data. The data were obtained from the Central Statistics Agency and the Financial Services Authority. The observation period covers 2015–2025 and includes 33 provinces in Indonesia. The data analysis method used is descriptive quantitative analysis, assisted by EViews 12 software. The model applied in this study is the Random Effects Model (REM). The results indicate that Islamic financing has a negative and significant effect on poverty, education has a negative and significant effect on poverty, and inequality has a positive and significant effect on poverty.